Children's Hospital Ambulatory Response to the 2019 Novel Coronavirus Disease (COVID-19) Pandemic. Issue 3 (July 2021) - Harahsheh, Ashraf S.; Selekman, Rachel E.; Simpson, Joelle N.; Cronin, Ileen; Cady, Rebecca F.; Martin, Benjamin D.; Mbwana, Juma; Biddle, Cara L.; Kalloo, Naida; Sharma, Hemant; Ricks, Jeanne R.; Helmandollar, Carole; et al.
Abstract : The 2019 novel coronavirus disease (COVID-19) pandemic produced an abrupt and near shutdown of nonemergent patient care. Children's National Hospital (CNH) mounted a multidisciplinary, coordinated ambulatory response that included supply chain management, human resources, risk management, infection control, and information technology. To ensure patient access, CNH expanded telemedicine and instituted operational innovations for outpatient procedures. While monthly in-person ambulatory subspecialty visits decreased from 25 889 pre-COVID-19 to 4484 at nadir of the COVID-19 pandemic, telemedicine visits increased from 70 to 13 539. Further studies are needed to assess the impact of innovations in health care delivery and operations that the crisis prompted.